Exit, exclusion, and parallel currencies in the euro area - Helmut Siekmann (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2015)
[Introduction ...] The following questions which are closely related to each other but deserve a distinctively different treatment have to be answered: I. Is it legally possible for a Member State to leave the eurozone? II. May Member State introduce a new currency parallel to the euro? III. Can a Member State be excluded from the eurozone or the Monetary Un-ion? IV. May permission be granted to introduce a new currency in a Member State of the eurozone? V. What are the consequences of an illegal exit from the eurozone?
urn:nbn:de:hebis:30:3-393978
Keywords: 330